Plasma‐free amino acid profiles in dogs with hepatocellular carcinoma. (8th May 2019) - Leela‐arporn, Rommaneeya; Ohta, Hiroshi; Tamura, Masahiro; Nagata, Noriyuki; Sasaoka, Kazuyoshi; Dermlim, Angkhana; Nisa, Khoirun; Osuga, Tatsuyuki; Morishita, Keitaro; Sasaki, Noboru; Takiguchi, Mitsuyoshi
Abstract: Background: Metabolomic analysis using blood samples has been suggested to be useful for the early detection of cancer. Among metabolites, plasma‐free amino acid (PFAA) profiles are potential diagnostic biomarkers for several diseases including cancer. However, the relationship between PFAA concentrations and liver tumors in dogs remains unknown. Objective: To determine the characteristics of PFAA profiles of dogs with hepatocellular carcinoma (HCC) and correlated clinical features. Animals: Thirty‐four client‐owned dogs diagnosed with HCC (n = 26) and benign liver diseases (n = 8) and 11 age‐matched healthy dogs. Methods: Prospective study using heparinized blood samples from fasted dogs. Plasma was deproteinized, and the concentrations of 21 amino acids were measured using an automated high‐performance liquid chromatography amino acid analyzer. Results: Plasma glutamic acid concentrations were significantly different among groups ( P  < .0024 after Bonferroni correction). Compared to healthy dogs, dogs with HCC and benign liver diseases had significantly higher concentrations of glutamic acid by post hoc analysis. However, no significant difference in the PFAA profiles of HCC and benign liver diseases were detected. In addition, preoperative and postoperative PFAA profiles of dogs with HCC were not significantly different. Conclusions and Clinical Importance: Increased glutamic acid concentrations might play a role in the development or be a consequence of liver tumor formation. However, PFAA profiles of HCC could not be differentiated from those of benign lesions. In addition, glutamic acid concentrations did not change after surgical resection. These results indicate that PFAA profiles may not be useful biomarkers for detecting HCC in dogs.